Evaluación de la Gestión del Desarrollo Turístico en le Parroquia el Rosario, cantón Guano, provincia de Chimborazo, durante el año 2012 - Osejo Vallejo, Rosa Edith (2015)
Today more and more people seek to interact in nature and leave behind the pace of cities saturated by traffic and smog because it lacks of natural recreational areas. In this sense, such outdoor activities practices multiply. In the recreational or competitive sports field you can find different activities, cycling is one of them. There is a huge concern for the impact that mankind causes to the environment and therefore have developed conservation proposals, less contamination and more physically activity, being one of them the construction permanent of recreational bike paths. The province of Chimborazo is located in the center of the inter-Andean road, its capital Riobamba is better known as the Sultan of the Andes, surrounded by four volcanoes: Chimborazo (Ecuador's highest), Tungurahua, Altar and a group of mountains not volcanic called Cubillines. Composed of ten counties: Penipe, Alausí, Chunchi, Guano, Riobamba, Chambo, Cumandá, Pallatanga, Colta, and Guamote, its altitude ranges from 320 m in the area of Cumandá up to 6310 meters at the highest summit of Chimborazo. Guano, better known as Canton of watershed is divided by the river of the same name (Guano River) in two urban counties: The Matriz and El Rosario plus nine rural counties, is located 8 km from the provincial capital Riobamba, considered craft center for the manufacture of handmade rugs, clothing of leather, and very famous for its typical gastronomic diversity of Ecuador. The parish Rosary is a privileged place to develop sports tourism for its proximity to Riobamba and its tourist attractions found along its route in implementing the " Touristic Sport Bikeway: La Ruta del Fraile" project, which aims to create a circuit cycling to motivate and reactivate tourism development in this county, where the bike path will serve to increase the level of visitation to the county and being a strategic solution for the multiplier effect that involves developing tourism. To implement the proposed recreational bike path, three strategic defined objectives have been defined with its respective activities and outcome indicators. The final output of the marketing mix was combined by producing flyers, billboards, written notices and authorization of the event organizing, it is a documented experience of a route that can be visited and be traveled by bike lovers trying to justify tourists and athletes to cross the Rosary county by bike, discovering beautiful scenery, sharing the friendliness of its people with the security of being backed by institutions that ensure their welfare during the trip without risk of accidents and contributing to "Leave No Trace in the places we travel. "(NDR. Ministry of Tourism).